Courageous training : bold actions for business results - Mooney, Tim, 1955- (BK business book., 2008)
Based on four years of Advantage Performance Group's work, and featuring real-life stories and several case studies, this book shares the process, the journey and the professional courage these HRD professionals took to ensure that they were helping their organisations achieve business results.